(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
In this article, the following activities are listed as being against Islamic finance: Risks, gharar, or uncertainty, and activities, or numerous opinions about Islamic financial institutions and gambling-related issues. There will be opinions and remarks about Islamic financing as the article is read. Islamic nations’ banks have unique qualities. That is, it is required to draw the resource entrusted to you based on the principles of Islam in order to grant a loan based on those principles. In other words, you might not be granted a loan if it is founded on Islamic principles and attracts interest deposits. because deposit attraction violates Islamic principles. First and foremost, in this regard, we need to work on raising awareness of Islamic financing